Does bank market power affect SME financing constraints? - Robert M. Ryan; Conor M. O'Toole; Fergal McCann (The Economic and Social Research Institute (ESRI), 2013)
This paper examines the extent to which bank market power alleviates or magnifies SME credit constraints using a large panel dataset of more than 118,000 SMEs across 20 European countries over the period 2005-2008. To our knowledge, this is the first study to examine bank market power and SME credit constraints in an international, developed economy setting. Moreover, our study is the first to address a number of econometric considerations simultaneously, in particular by controlling for the availability of profitable investment opportunities using a structural Q model of investment. Our results strongly support the market power hypothesis, namely, that increased market power results in increased financing constraints for SMEs. Additionally, we find that the relationship exhibits heterogeneity across firm size and opacity in a manner that suggests that the true relationship between bank market power and financing constraints might not be fully explained by the existing theory. Finally, we find that the effect of bank market power on financing constraints increases in financial systems that are more bank dependent.
Keywords: 330